A Comparative Study on the Thermal Behavior of Second-Life and New Batteries under Realistic Operating Conditions - Ozdemir, Ozlem; Ates, Yavuz; Boynuegri, Ali Rifat; Turan, Feyza (IEEE, 2025)
With the increasing interest in second-life batteries (SLBs) and the growing importance of energy storage in renewable energy systems, evaluating the technical and thermal analysis of SLB integration has become essential. This study presents a comprehensive technical and thermal analysis of integrating SLBs into PV-based energy storage systems (ESS). The thermal behavior of SLBs was investigated under realistic operating conditions, and the required cooling system capacity was determined accordingly. The dynamic degradation of battery capacity was modeled throughout the system's lifetime, and daily charge-discharge Crates were calculated using an energy management algorithm designed to maximize daily profit. These values were then used to estimate daily heat generation and the corresponding cooling demand. A comparison was made between SLBs and new batteries in terms of their thermal performance and cooling requirements. Results showed that the cooling energy consumption (BTU/h) for SLBs is up to 6.9 times higher than that for new batteries, primarily due to increased internal resistance. While this increases operational cooling costs, it should not overshadow the economic advantages offered by SLBs, particularly their significantly lower acquisition and replacement costs. The findings highlight the importance of evaluating SLB integration using a holistic approach that accounts for both technical and economic aspects, rather than focusing solely on individual parameters such as thermal load or energy consumption.
Keywords: Battery degradation; energy storage; second-life battery; thermal management; Energy & Fuels; Engineering; Telecommunications